Impacts on post-COVID-19 sequelae: A Systematic Review - Jannathul Firdous, Nang Thinn Thinn Htike, Alia Afiqah Binti Zainudin, Azizah Haziqah Binti Azizah Ariffin, Mohamad Aidel Mukhriz Bin Mohd Burhan, Nurin Zahirah Binti Zulhisham (Journal of Applied Pharmaceutical Science, 2022)
Concerns on whether or not coronavirus disease 2019 (COVID-19) can cause long-term impact are rising since many aspects of the disease are still under investigation. This systemic review was carried out to recognize the post- COVID-19 sequelae infection in various body systems and to analyze the comorbidities in survivors who suffered long-term impacts. The choice of words used to search is “post-COVID-19,” “COVID-19,” and “SARS-CoV-2 infection.” A total of 1,282 articles were extracted. Reports suggested that a wide range of sequelae were faced by the survivors which affected various systems, mainly the respiratory, gastrointestinal, nervous, cardiovascular, and musculoskeletal systems, while rarely affect other systems such as the endocrine, vascular, renal, and urogenital systems. Comorbidities are involved in determining the harshness of sequelae and the persistence of symptoms of post-severe acute respiratory syndrome coronavirus-2 infection. COVID-19 survivors may present with different symptoms and conditions that vary from mild symptoms to severe and rare conditions. It is crucial to understand the sequelae of post-COVID-19 for prevention and help to establish pandemic control strategies and rehabilitation needs.ß
Keywords: Consequences, cardiovascular disorder, mortality, post-acute infection, respiratory symptoms